2018
DOI: 10.7554/elife.36493
|View full text |Cite
|
Sign up to set email alerts
|

Reduced auditory cortical adaptation in autism spectrum disorder

Abstract: Adaptation is a fundamental property of cortical neurons and has been suggested to be altered in individuals with autism spectrum disorder (ASD). We used fMRI to measure adaptation induced by repeated audio-visual stimulation in early sensory cortical areas in individuals with ASD and neurotypical (NT) controls. The initial transient responses were equivalent between groups in both visual and auditory cortices and when stimulation occurred with fixed-interval and randomized-interval timing. However, in auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 57 publications
3
60
0
Order By: Relevance
“…Our study included 28 young adult participants on the autism spectrum (18 males, 10 females), and 35 NT comparison participants (21 males, 14 females). Data from these participants with ASD [58][59][60] and NTs 12,[58][59][60][61] were included in our recently published work. All participants were assessed by clinicians with extensive experience with ASD, under the supervision of a doctorallevel clinical psychologist who had achieved research reliability in the gold standard tools used to diagnose ASD.…”
Section: Methodsmentioning
confidence: 99%
“…Our study included 28 young adult participants on the autism spectrum (18 males, 10 females), and 35 NT comparison participants (21 males, 14 females). Data from these participants with ASD [58][59][60] and NTs 12,[58][59][60][61] were included in our recently published work. All participants were assessed by clinicians with extensive experience with ASD, under the supervision of a doctorallevel clinical psychologist who had achieved research reliability in the gold standard tools used to diagnose ASD.…”
Section: Methodsmentioning
confidence: 99%
“…This would therefore suggest that to the autistic brain, incoming sensory input would seem more novel, and less familiar. In keeping with this hypothesis, autistic listeners have been found to show less auditory adaptation to repeated sounds (Millin et al, 2018), which is perhaps suggestive of an impairment in predictive mechanisms (Sinha et al, 2014). Similarly, Skewes and Gebauer found suboptimal integration of sensory evidence and prior perceptual knowledge in an auditory localization task in adults with autism (Skewes & Gebauer, 2016).…”
Section: Introductionmentioning
confidence: 81%
“…We were limited by whole-brain analyses as the inclusion of region-specific analyses would violate the assumptions of the coordinate-based voxel-wise meta-analysis (Radua & Mataix-Cols, 2009;Wager et al, 2007, p. 20;Eickhoff et al, 2012) By excluding hypothesis-driven fMRI studies employing ROI analyses, we may be missing out on subtle, low-level neural differences identified in the primary sensory cortices. Using ROI-based approaches, studies have identified early, autism-specific neural responses in a number of regions including: the primary visual cortex and middle temporal gyrus during visual global motion perception (Robertson et al, 2014) ; intraparietal sulcus, primary and secondary visual cortex, precuneus, cerebellum and middle temporal gyrus during passive and active visual movement tracking (Takarae et al, 2014) ; extrastriate population receptive fields during visual stimulation (Schwarzkopf et al, 2014); and the primary auditory cortices as a result of audiovisual adaptation (Millin et al, 2018) . Although these regions feature in our meta-analysis findings, we note that the exclusion of such studies may have attenuated the effects of some regions commonly activated during autistic perception.…”
Section: Limitationsmentioning
confidence: 99%